DISCOURSE ANALYSIS: UNCOVERING MEANING AND PRAGMATICS IN TERE LIYE NOVELS “PULANG PERGI” - Elyana Feronica Manurung; Rahel Raphita Sinabutar (Pondok Pesantren Baitul Quran, 2024)
This article delves into the depths of discourse analysis to uncover the nuanced layers of meaning and pragmatics embedded within Tere Liye's novel